Embryonic development and hatching of Lo%o duvaucelii Orbigny (Loliginidae, Cephalopoda) in the laboratory - Asokan, P K; Kakati, V S (Indian Journal of Fisheries, 2011)
The bulk of the cephalopod production in Indian waters cwnprises cuttlefishes (60%) and the rest consists of squids and a negligible quantity of octopods (Silas 1986). The biology and fishery of cephalopods have attracted the attention of many workers in India (Rao 1954, Alagarswami 1966, Silas 1968, 1986, Sarvesan 1969, Silas et al. 1982, Sivalingam and Pillai 1983).